USING METHODS OF SOLARIZATION, BIO-FUMIGATION, BURNING AND KEEP DRYING SOIL CONTROL ROOT- KNOT NEMATODES ON LETTUCES, IN LAM DONG - Văn Ngọc Thủy; Lê Bá Lê; Trần Thị Minh Loan (Tạp chí Khoa học Đại học Đà Lạt)
Root-knot nematodes (Meloidogyne sp.) are an important plant – parasitic group on green lollo lettuce. Experiments, included solarizion, bio-fumigation, burning and keep drying soil were carried out to control root-knot nematodes on lettuces in Lamdong province. The results showed that burning method was the most effective (in soil) with only 28 juveniles/100g of soil and 96.75% after treating compared to the control with 1312 nematodes/100g of soil. The infection proportion of root-knot nematodes (1.433) and the number of juveniles of root-knot nematodes (201 juveniles/5g of root) in the burning were the lowest. Therefore, the height and the yield of crop treated with this method were the highest, proved by 25.99 cm and 30.25 tons/ha, respectively. In contrast, the root infection proportion in the control was the highest, accounting for 5.733 while the figures for the height (18.8 cm) and the yield of crop (15.93 tons/ha) were the lowest.